Human Enterovirus 68 Interferes with the Host Cell Cycle to Facilitate Viral Production - Wang, Zeng-yan; Zhong, Ting; Wang, Yue; Song, Feng-mei; Yu, Xiao-feng; Xing, Li-ping; Zhang, Wen-yan; Yu, Jing-hua; Hua, Shu-cheng; Yu, Xiao-fang (Frontiers in Cellular and Infection Microbiology, 2017)
Enterovirus D68 (EV-D68) is an emerging pathogen that recently caused a large outbreak of severe respiratory disease in the United States and other countries. Little is known about the relationship between EV-D68 virus and host cells. In this study, we assessed the effect of the host cell cycle on EV-D68 viral production, as well as the ability of EV-D68 to manipulate host cell cycle progression. The results suggest that synchronization in G0/G1 phase, but not S phase, promotes viral production, while synchronization in G2/M inhibits viral production. Both an early EV-D68 isolate and currently circulating strains of EV-D68 can manipulate the host cell cycle to arrest cells in the G0/G1 phase, thus providing favorable conditions for virus production. Cell cycle regulation by EV-D68 was associated with corresponding effects on the expression of cyclins and CDKs, which were observed at the level of the protein and/or mRNA. Furthermore, the viral non-structural protein 3D of EV-D68 prevents progression from G0/G1 to S. Interestingly, another member of the Picornaviridae family, EV-A71, differs from EV-D68 in that G0/G1 synchronization inhibits, rather than promotes, EV-A71 viral replication. However, these viruses are similar in that G2/M synchronization inhibits the production and activity of both viruses, which is suggestive of a common therapeutic target for both types of enterovirus. These results further clarify the pathogenic mechanisms of enteroviruses and provide a potential strategy for the treatment and prevention of EV-D68-related disease.